Impaired night-time mobility in patients with Parkinson’s disease: a systematic review - Li, Shengyiwen; Lin, Qingyang; Bao, Yannan; Feng, Yichen; Li, Dianyou; Zhang, Chencheng (Frontiers in Aging Neuroscience, 2023)
Impaired bed mobility (IBM) is a symptom characteristic of patients having difficulty intentionally moving their bodies during nighttime sleep. IBM is one of the most common nocturnal symptoms of Parkinson’s disease (PD) and may lead to extreme pain and even death; it also increases the burden on the patients’ caregivers. In this systematic review, we included 19 studies involving a total of 1,407 patients with PD to observe the causes, assessment methods, and treatment options for IBM. We conclude that the extent of IBM is positively correlated with the severity of symptoms such as disease duration, dyskinesia and decreased sleep quality in patients with PD, and the evidence implies that IBM may be able to serve as a prodromal feature in the development of PD. IBM probably results from low nocturnal dopamine concentrations, reduced function of the spinal tract, torque problems in the muscles, and aging. Therefore, treatment is mostly based on continuously increasing the patient’s nocturnal dopamine concentration, while deep brain stimulation (DBS) also has a mitigating effect on IBM. Both scales and sensors are commonly used to measure the severity of IBM, the wearable device monitoring and scales being updated makes measurements easier and more accurate. The future of the advancement in this field lies in the use of more family-oriented devices (such as smart phones or watches and bracelets, etc.) to monitor IBM’s symptoms and select the appropriate therapeutic treatment according to the severity of the symptoms to relieve patients’ suffering.